Communication skills for effective dementia care : a practical guide to communication and interaction training (CAIT) - James, Ian Andrew, 1963-; Gibbons, Laura (Jessica Kingsley Publishers, 2019)
Effective communication is critical for everyone, and this insightful book teaches the skills needed by healthcare staff in their day-to-day interactions with people with dementia and their families. Often when people with dementia exhibit agitation, it is an indication that their needs are not people met. The authors illustrate the key aspects of communication for the development of a skilled and confident workforce, capable of providing thoroughly effective care that reduces levels of agitation in people with dementia--back cover.